Are the first hours of stages a determining aspect in cyclists` performance? Analysis of power output in Pro Team vs. World Tour riders - Zabala, M.; Mateo-March, M.; Barranco-Gil, D. (Journal of Science and Cycling, 2024)
Introduction Grand Tour road cycling races consist of multiple stage types that place varying physiological demands on riders. Teams are classified by the UCI as either World Tour (WT), the highest professional level, or ProTeam (PT) who require wildcard invitations. Previous research has found WT riders outperform PT riders, but no studies have directly compared internal and external load between categories. As fatigue influences subsequent performance, the aims were to describe and compare load during the initial hours of competition between WT and PT riders.